2017
DOI: 10.1194/jlr.m076349
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ceramide metabolism are essential in Madin-Darby canine kidney cell differentiation

Abstract: Ceramides (Cers) and complex sphingolipids with defined acyl chain lengths play important roles in numerous cell processes. Six Cer synthase (CerS) isoenzymes (CerS1-6) are the key enzymes responsible for the production of the diversity of molecular species. In this study, we investigated the changes in sphingolipid metabolism during the differentiation of Madin-Darby canine kidney (MDCK) cells. By MALDI TOF TOF MS, we analyzed the molecular species of Cer, glucosylceramide (GlcCer), lactosylceramide (LacCer),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The quantitative analysis shows that cells in progress to differentiation, in response to treatment with SK inhibitors increased the incorporation of [ 14 C] palmitic acid associated with total sphingolipids ( Fig 7A ). The analysis of the individual sphingolipids, whose identity was determined by mass spectrometry [ 16 ], showed that the treatment of cells with t-DHS evoked an increase in the radioactivity associated with Cer (4.9-fold). A small but significant increase was observed in both GluCer (1.3-fold) and SM (2.3-fold).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The quantitative analysis shows that cells in progress to differentiation, in response to treatment with SK inhibitors increased the incorporation of [ 14 C] palmitic acid associated with total sphingolipids ( Fig 7A ). The analysis of the individual sphingolipids, whose identity was determined by mass spectrometry [ 16 ], showed that the treatment of cells with t-DHS evoked an increase in the radioactivity associated with Cer (4.9-fold). A small but significant increase was observed in both GluCer (1.3-fold) and SM (2.3-fold).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that, by modulating the expression and activity of sphingolipid metabolic enzymes, MDCK cells can direct the formation of the final metabolites that define cellular fate. In fact, we have reported that SK is highly expressed in proliferative state, thus maintaining cell proliferation and survival, while in differentiated cells, increased expression and activity of SM synthase and GluCer synthase ensure the establishment and preservation of cell-cell adhesion and mature apical membrane domain, typical of differentiated renal collecting duct cells [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies (Favale et al, 2007;Pescio et al 2012Pescio et al , 2017Casali et al, 2013) have demonstrated that MDCK cultures subjected to high NaCl-hyperosmolar medium accelerate their polarization-differentiation process. Thus, after 48-72 h of hyperosmolar treatment cells undergo morphological changes from a fibroblast-like phenotype into a polarized epithelial phenotype that includes primary cilium formation on apical membranes almost reminiscent of medullary collecting duct cells.…”
Section: Discussionmentioning
confidence: 98%